2000
DOI: 10.4049/jimmunol.164.12.6566
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human γ-Tryptases, Novel Members of the Chromosome 16p Mast Cell Tryptase and Prostasin Gene Families

Abstract: Previously, this laboratory identified clusters of α-, β-, and mast cell protease-7-like tryptase genes on human chromosome 16p13.3. The present work characterizes adjacent genes encoding novel serine proteases, termed γ-tryptases, and generates a refined map of the multitryptase locus. Each γ gene lies between an α1H Ca2+ channel gene (CACNA1H) and a βII- or βIII-tryptase gene and is ∼30 kb from polymorphic minisatellite MS205. The tryptase locus also contains at least four tryptase-like pseudogenes, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
122
0
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 42 publications
4
122
0
2
Order By: Relevance
“…Cloning of its human ortholog followed shortly thereafter, and expression studies confirmed its localization in mouse and human MCs (15,18,20). Fifteen single nucleotide polymorphisms have been identified in the hPrss31 gene, which result in amino acid changes at residues 23, 123, 202, and 252 in the protease's mature domain.…”
Section: Mc-restricted Granule Proteases and Proteoglycansmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloning of its human ortholog followed shortly thereafter, and expression studies confirmed its localization in mouse and human MCs (15,18,20). Fifteen single nucleotide polymorphisms have been identified in the hPrss31 gene, which result in amino acid changes at residues 23, 123, 202, and 252 in the protease's mature domain.…”
Section: Mc-restricted Granule Proteases and Proteoglycansmentioning
confidence: 99%
“…Although Prss34 is expressed by interleukin (IL) 3-differentiated mouse bone marrow-derived MCs (mBMMCs), it remains to be seen whether tissue MCs express this tryptase. The syntenic human tryptase locus resides ϳ1.2 megabases from the telomeric end of chromosome 16p13.3 (17)(18)(19)(20). This region has been difficult to sequence because of its high rate of mutation and recombination (21).…”
Section: Mc-restricted Granule Proteases and Proteoglycansmentioning
confidence: 99%
“…Studies using recombinant human pro-␣-chymase suggest that DPPI can activate prochymase in vitro by removing the activation dipeptide (6). Tryptases also are a diverse group of structurally related proteases that include ␣, ␤, and ␥ isoforms in humans (12,13) and two or three tryptases (mMCP-6, mMCP-7, and transmembrane/␥) in mice (14). MMCP-7 is not expressed in C57BL/6 mice, and thus, its expression is strain-dependent (15).…”
mentioning
confidence: 99%
“…All populations of MCs examined to date store in their secretory granules various combinations of carboxypeptidase A, chymases, and tryptases ionically bound to serglycin proteoglycans that contain either heparin or highly sulfated chondroitin glycosaminoglycans. Human MCs express at least five distinct tryptases, and the cDNAs and genes have been isolated that encode human tryptases ␣, ␤I, ␤II, and ␤III, as well as a less homologous transmembrane tryptase (5)(6)(7)(8)(9)(10). Mapping and sequencing analysis of the region of human chromosome 16, where these genes reside, has revealed the presence of additional genes in the family (9,11), but it remains to be determined whether or not any of these genes encode enzymatically active proteases.…”
mentioning
confidence: 99%